KAITAN MANAJEMEN PENGARSIPAN DENGAN MANAJEMEN ADMINISTRASI PERKANTORAN LAINNYA DAN APLIKASINYA PADA TATA USAHA SUATU PROGRAM DIII - Ida Nuraida (Bina Ekonomi, 2005)
Every company and institution hat files. Files save data and information of the company's daily activities and other company's important records. Filing work exists  in every department  of organization. Filling should not be underestimated by employees of every department in every company. They should understand  the importance of filling management, which is a part of administrative office management. Filing cannot be avoided in every office work and filling affects the effectiveness and efficiency of companies. Filing management cannot be separated, with office media (mails, forms reports ), procedure, management information system of the company and the management  of handling / recording office documents. Data and information can filed , by manual or electronic  filing systems. The progress of technology effects the tools of filling digitalization. In general, files could  be backed up through digitalization . However, some files require to be saved manually as to guarantee future business, as It is compulsory according to regulations and laws, and this action is required to avoid fraud for some illegal operations as well. The example of this explanation is illustrated by a research on filing management of academic and student files in a program diploma.